2021
DOI: 10.3389/fonc.2020.558428
|View full text |Cite
|
Sign up to set email alerts
|

Preoperatively Estimating the Malignant Potential of Mediastinal Lymph Nodes: A Pilot Study Toward Establishing a Robust Radiomics Model Based on Contrast-Enhanced CT Imaging

Abstract: PurposeTo establish and validate a radiomics model to estimate the malignancy of mediastinal lymph nodes (LNs) based on contrast-enhanced CT imaging.MethodIn total, 201 pathologically confirmed mediastinal LNs from 129 patients were enrolled and assigned to training and test sets. Radiomics features were extracted from the region of interest (ROI) delineated on venous-phase CT imaging of LN. Feature selection was performed with least absolute shrinkage and selection operator (LASSO) binary logistic regression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, it has been reported that PTX could promote lymphatic metastasis of breast cancer in some cases, besides inhibiting tumour growth 4 , 5 . Lymphatic metastasis is a significant basis for determining clinical treatment and predicting the prognosis of patients with tumours after treatment 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that PTX could promote lymphatic metastasis of breast cancer in some cases, besides inhibiting tumour growth 4 , 5 . Lymphatic metastasis is a significant basis for determining clinical treatment and predicting the prognosis of patients with tumours after treatment 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The patients enrolled in the present study were divided into training and validation cohorts. Multivariate logistic regression analysis with the backwards method ( 25 ) was used to select independent predictors from clinical features, including consolidation, age, family history, sex and smoking history, in the training cohort, and receiver operating characteristic (ROC) curves were plotted. Area under the ROC curve (AUC) values represent the predictive ability of the clinical prediction model.…”
Section: Methodsmentioning
confidence: 99%
“…For medical images with small datasets, radiomics is more suitable. Recently, some researchers have used radiomics based on CT or PET/CT images for the diagnosis of benign and malignant LNs ( 12 , 24 , 25 ). Most studies of LN benignity and malignancy are single-centre studies, and so reproducibility and generalisability are not guaranteed.…”
Section: Introductionmentioning
confidence: 99%